How to chair a department - Dettmar, Kevin J. H., 1958- (Higher ed leadership essentials., 2022)
"A practical, accessible handbook for chairing a department. Over the course of a typical academic career, most faculty will serve at least one term as chair of a department. It's a leadership and service role that's at the very heart of faculty satisfaction and student success, yet few receive any training on how to do the job. How to Chair a Departmentis a practical, accessible handbook for new and prospective chairs, providing both principles and practices for effective departmental leadership. Based on his dozen years of chairing departments, Kevin Dettmar provides invaluable advice on: * hiring tenure-track and visiting faculty * mentoring faculty colleagues at every stage of their careers * working with staff and other departmental administrators * managing department resources and budgets * meeting the needs of students * dealing with stress and conflict * connecting the department to the larger university or college as a whole * overseeing the department's curricula * maintaining a scholarly or creative profile * preparing for career moves after chairing a department How to Chair a Departmentdemystifies this important faculty position and argues that the role of chair, though sometimes seen as a burden, can prove to be a genuine opportunity for personal and professional growth."--